PERANAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR IPS - Sulfemi, wahyu Bagja; Mayasari, Nova (LPPM Universitas Terbuka, 2019)
Classroom Action Research was carried out to explain the impact of value clarification technique to improve elementary student learning motivation, interest and  achievement in social studies.  This technique was in two cycles, involving29students, 10 male and  and 19 female. The theme discusses was the important family events. The results of pre-cycle learning activities were obtained with a mean grade of 56,38, there are 10 students (34,48%) who achieved the minimum score of mastery. The observationreveals that students who are courageo us and are able to answer the teacher's questions correctly are 9 people or 31,03%. The data from Cycle 1 indicates a better result, with the class average of 68,28, and  17students or 58,62% achieved the minimum score of mastery. The observation also shows an increase of students whowere able to answer the teacher's questions correctly, which is 16 students or 55,17%. The Cycle 2 activity which used Value Clarification Technique (VCT), suplemented audio visual media obtains a better result with a mean of 86,72, and 27 students (93,10 %) who achieved the minimum score of mastery. The observation also shows a better percentage, 26 people or 89.66% who are capable of answering teacher questions correctly. It can be concluded thatValue Clarification Technique (VCT) using audio visual media can improve student motivation and learning achievement. Penelitian Tindakan Kelas (PTK) ini mempunyai tujuan menganalisis penggunaan model value clarification technique untuk meningkatkan motivasi, minat, dan hasil Belajar IPS siswa Sekolah Dasar. Kegiatan pembelajaran Prasiklus menghasilkan rerata kelas 56,38, dengan peserta didik yang tuntas sebayak 10 atau 34,48%. Hasil pengamatan menunjukkan siswa yang memiliki keberanian dan mampu jawab pertanyaan guru dengan benar baru 9 orang atau 31,03%.  Dari Kegiatan Siklus 1 diperolehrerata kelas 68,28, dengan peserta didik yang tuntas sebayak 17 orang atau 58,62%. Hasil pengamatan menunjukkan siswa yang memiliki keberanian dan mampu menjawab pertanyaan guru dengan benar meningkat, mencapai 16 orang atau 55,17%. Kegiatan Siklus 2 yang menggunakan Value Clarification Technique (VCT) dengan berbantuan media audio visual  diperoleh hasil rerata kelas 86,72 dengan peserta didik yang tuntas sebayak 27 orang peserta didik atau 93,10 Hasil pengamatan menunjukkan siswa yang memiliki keberanian dan mampu jawab pertanyaan guru dengan benar mencapai 26 orang atau 89,66%. Dapat disimpulkan bahwa penggunaan model pembelajaran Menggunakan Value Clarification Technique (VCT) berbantuan audio visual meningkatkan motivasi peserta didik dalam proses belajar dan hasil belajarnya.